A new macro-model to analyse the combined in-plane/out-of-plane behaviour of unreinforced and strengthened infill walls. (1st January 2022) - Donà, Marco; Minotto, Massimiliano; Verlato, Nicolò; da Porto, Francesca
Abstract: Reinforced concrete (RC) frame structures infilled with clay masonry walls represent a common construction practice worldwide. However, the significant interaction between in-plane (IP) and out-of-plane (OOP) response of the infill walls, and their brittle behaviour, can increase the seismic vulnerability of the building to both local and global mechanisms. Therefore, it is necessary to develop adequate tools to assess the seismic performance of infill panels. To this end, this paper presents a new macro-model for evaluating the IP/OOP behaviour of infill walls. The model consists of four strut elements, two for each diagonal of the wall, and two equal OOP masses placed in the centre of the panel; each strut is made of two beam-column elements that allow for the creation of a plastic hinge at the mid-span, where the non-linearity due to the IP/OOP interaction is concentrated and modelled through a nonlinear fibre section. The model is experimentally calibrated for four types of thin clay masonry panels, one unreinforced and three strengthened. To show the potential of the new infill model, a non-linear static analysis procedure is proposed for evaluating the lateral response of RC infilled frames. This simplified procedure is finally used in a parametric study that analyses various types of infilled frames. The results demonstrate the effectiveness of the proposed model, as well as of the strengthening solutions adopted to mitigate the IP/OOP interaction effects.